DE VUELTA A TRANSFORMACIONES DE LA TIERRA. LEYENDO A DONALD WORSTER DESDE AMÉRICA LATINA. - Castro Herrera, Guillermo (2012)
This article presents a re-reading the essay “Nuestra tierra” (Our Land) by Donald Worster, it takes place from the perspective that handles Latin America with regard to environmental history. The article starts from three basic ideas: structure and distribution of natural environments in the past, productive technology and intangible encounter between them. The ultimate goal is to confront the problem proposed by Worster about the cultural and political problems that Latin America is living, under the slogan: it’s time to start doing, not just to write.